Arthroplasty implant biomaterial particle associated macrophages differentiate into lacunar bone resorbing cells. Issue 6 (June 1996) - Pandey, R; Quinn, J; Joyner, C; Murray, D W; Triffitt, J T; Athanasou, N A
Abstract : OBJECTIVE: To study the pathogenesis of aseptic loosening: in particular, to determine whether macrophages responding to particles of biomaterials commonly used in arthroplasty surgery for arthritis are capable of differentiating into osteoclastic bone resorbing cells, and the cellular and hormonal conditions required for this to occur. METHODS: Biomaterial particles (polymethylmethacrylate, high density polyethylene, titanium, chromium-cobalt, stainless steel) were implanted subcutaneously into mice. Macrophages were isolated from the foreign body granulomas that resulted, cultured on bone slices and coverslips, and assessed for both cytochemical and functional evidence of osteoclast differentiation. RESULTS: Tartrate resistant acid phosphatase (TRAP) negative macrophages isolated from granulomas containing particles of all types of biomaterial composition were capable of differentiating into TRAP positive cells capable of extensive lacunar bone resorption (assessed by scanning electron microscopy). The presence of both UMR106 rat osteoblast-like cells and 1, 25-dihydroxy vitamin D3 was necessary for this to occur. CONCLUSION: All implant materials produce wear particles that are the focus of a heavy foreign body macrophage response in the fibrous membrane between a loose implant component and the host bone undergoing resorption. These findings underline the importance of biomaterial wear particle generation and the macrophage response to different types of biomaterial wear particles in the pathogenesis of aseptic loosening.